If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + -1z)(2z + 5) = 0 Reorder the terms: (6 + -1z)(5 + 2z) = 0 Multiply (6 + -1z) * (5 + 2z) (6(5 + 2z) + -1z * (5 + 2z)) = 0 ((5 * 6 + 2z * 6) + -1z * (5 + 2z)) = 0 ((30 + 12z) + -1z * (5 + 2z)) = 0 (30 + 12z + (5 * -1z + 2z * -1z)) = 0 (30 + 12z + (-5z + -2z2)) = 0 Combine like terms: 12z + -5z = 7z (30 + 7z + -2z2) = 0 Solving 30 + 7z + -2z2 = 0 Solving for variable 'z'. Factor a trinomial. (6 + -1z)(5 + 2z) = 0Subproblem 1
Set the factor '(6 + -1z)' equal to zero and attempt to solve: Simplifying 6 + -1z = 0 Solving 6 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1z = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1z = 0 + -6 -1z = 0 + -6 Combine like terms: 0 + -6 = -6 -1z = -6 Divide each side by '-1'. z = 6 Simplifying z = 6Subproblem 2
Set the factor '(5 + 2z)' equal to zero and attempt to solve: Simplifying 5 + 2z = 0 Solving 5 + 2z = 0 Move all terms containing z to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2z = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2z = 0 + -5 2z = 0 + -5 Combine like terms: 0 + -5 = -5 2z = -5 Divide each side by '2'. z = -2.5 Simplifying z = -2.5Solution
z = {6, -2.5}
| 0.5+16=4-0.6 | | 0.12y+0.09(y+5000)=1290 | | (r-5)(r-1)= | | 5[n+10]=10 | | 7y-10y-11+3=7 | | 4(2x-4)=8x+k | | y(2-x)= | | 5n+24=8-3 | | -4x-9=13 | | x^2y-3xy=0 | | (y+6)(y+3)= | | 12y+5(y+-6)=4 | | 12y^2+5y=2 | | 2c+8=3c | | 21.24-x(0.0625)=x | | 10-6x=32 | | -17.1=-4.8 | | 6x-8w+2x+8y+3y+5w= | | 6x+0.4y=4.2 | | -20=4u+4 | | 6x+8w+2x+8y+3y+5w= | | W+(-5)=-4 | | 8w+18=56 | | 2sin^2x-7sinx-4=0 | | 5=-3+2w | | -t+2=8t-8-4t | | x-(-5)=5 | | cosx-secx=0 | | 0.8-4x=-0.4y | | (3x+1)=(x-6) | | 81-57=x | | 35x^2+12xy-32y^2=0 |